2017
DOI: 10.1007/s11250-017-1501-7
|View full text |Cite
|
Sign up to set email alerts
|

Growth traits of crossbreds of Ankole with Brown Swiss, Holstein Friesian, Jersey, and Sahiwal cattle in Rwanda

Abstract: The objective of the study was to compare body weights and growth from birth to 18 months of age of various groups of crossbred cattle born from 1999 to 2007, being crossbreds of Ankole (A) with Brown Swiss (B), Holstein Friesian (F), Jersey (J), and Sahiwal (S). Average weights were 26.5 kg at birth, 161 kg at weaning, and 226 kg at 18 months. Both season and sex significantly affected birth weight (BW), weight at 8 and 18 months (W8 and W18), and average daily gain from weaning to 18 months (ADG18) and, unli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
1
5
0
2
Order By: Relevance
“…Which may be due to the dams calved in autumn season would have inadequate feed and pastures during the previous season (summer), therefore results in birth weight decrease and weak body conditions of the pregnant dams during calving. This result in accordance with Kocak et al (2007 andManzi et al (2018). Thatcher et al (1986) whose indicated that thermal stress lead to reduce feed intake of dams and probably a reduction in the blood flow to the uterus may be the cause of the light birth weight of calves born in the dry season.…”
Section: Effect Of Year Of Calvingsupporting
confidence: 90%
“…Which may be due to the dams calved in autumn season would have inadequate feed and pastures during the previous season (summer), therefore results in birth weight decrease and weak body conditions of the pregnant dams during calving. This result in accordance with Kocak et al (2007 andManzi et al (2018). Thatcher et al (1986) whose indicated that thermal stress lead to reduce feed intake of dams and probably a reduction in the blood flow to the uterus may be the cause of the light birth weight of calves born in the dry season.…”
Section: Effect Of Year Of Calvingsupporting
confidence: 90%
“…An upper limit of suckled milk can be estimated based on how fast the calves grow. A previous study of calves at the three research stations included in this study found that the average daily weight gain was 0.4 kg/day (Manzi et al 2018 ). Based on Dove and Axelsen ( 1979 ), an estimated 10.8 kg milk is needed per kilogram of daily gain.…”
Section: Discussionmentioning
confidence: 81%
“…Program pelaksanaan kegiatan crossbreeding secara intensif di peternakan besar pada beberapa negara dilakukan khususnya pada ternak sapi, baik sapi pedaging maupun sapi perah (Bunning et al, 2019;Manzi et al, 2018;Schutt et al, 2009;Singh, 2016;Theunissen et al, 2014;Van Raden and Sanders, 2003). Terdapat dua keunggulan penting yang diperoleh dari program Corresponding author: jakaria_karman@yahoo.co.id DOI: https://doi.org/10.…”
Section: Pendahuluanunclassified
“…Cross-breeding pada sapi pedaging dan sapi perah memberikan dampak positif dan menghasilkan beberapa keuntungan (Weaber, 2015) baik dengan metode terminal crossing atau grading up (Singh, 2016). Persilangan antara bangsa sapi yang termasuk dalam Bos taurus dan Bos indicus intensif dilakukan dan memberikan pengaruh terhadap pertumbuhan (Manzi et al, 2018). Program cross-breeding sapi BB dengan sapi lokal khususnya sapi PO pada keturunan pertama (F 1 ) yang dilakukan di BET Cipelang Bogor belum pernah dievaluasi terkait dengan performa pertumbuhannya.…”
Section: Pendahuluanunclassified